53.8k views
0 votes
6-7(x+1)= -3(2-x)
How do you solve this?

1 Answer

6 votes

Step-by-step explanation

  • Given the equation.


6 - 7(x + 1) = - 3(2 - x)

  • Distribute/Simplify


6 - 7x - 7 = - 6 + 3x \\ - 1 - 7x = - 6 + 3x

  • Solve the equation for x-term by making x as the subject.


- 1 + 6 = 7x + 3x \\ 5 = 10x \\ (5)/(10) = x \\ (1)/(2) = x

  • Answer Check by substituting the value of x in the equation.


6 - 7( (1)/(2) ) - 7 = - 6 + 3( (1)/(2) ) \\ 6 - (7)/(2) - 7 = - 6 + (3)/(2) \Longrightarrow \sf{You \: \: can \: \: change \: \: sides \: \: to \: \: make \: \: it \: \: easier} \\ 6 - 7 + 6 = (7)/(2) + (3)/(2) \\ 5 = (10)/(2) \\ 5 = 5 \: \green{ \checkmark}

The equation is true for x = 1/2.

Answer


\large \boxed{x = (1)/(2) } \: \: \: \: \green{ \checkmark}

User Harshay Buradkar
by
5.8k points